COMPETITIVE STATE ANXIETY AND PERFORMANCE IN YOUNG MALE ARTISTIC GYMNASTS - George Dallas; Stelliou Charis; Theodorou Apostolos; Costas Dallas (University of Ljubljana Press (Založba Univerze v Ljubljani), 2023)
The purpose of this study was to investigate the competitive state anxiety and self-confidence on artistic gymnasts participating in the Greek national competition. 84 gymnasts, aged 9 - 11 years, completed the Competitive State Anxiety Inventory-2, one hour before the competition. The gymnasts, based on the total score they have received in all-around competition were divided into high and low performance, responded to the three subscales: Cognitive Anxiety, Somatic Anxiety, and Self-confidence. Results showed that there was significant difference in Self-confidence between high performance and low performance gymnasts. However, no significant differences were found in cognitive anxiety and somatic anxiety in these gymnasts. The Pearson coefficient revealed statistically significant between cognitive and somatic anxiety. The regression analysis failed to reveal any significant predictor of performance in these young male artistic gymnasts. The findings of the study underline the importance of examining competitive state anxiety and self-confidence in young male artistic gymnasts, mainly developing strategies to improve self-confidence to enable the athletes to better prepare for forthcoming competitions.